Epigenetic Programming and Fetal Metabolic Programming - Zhu, Ziqiang; Cao, Fang; Li, Xiaozhong (Frontiers in Endocrinology, 2019)
Fetal metabolic programming caused by the adverse intrauterine environment can induce metabolic syndrome in adult offspring. Adverse intrauterine environment introduces fetal long-term relatively irreversible changes in organs and metabolism, and thus causes fetal metabolic programming leading metabolic syndrome in adult offspring. Fetal metabolic programming of obesity and insulin resistance plays a key role in this process. The mechanism of fetal metabolic programming is still not very clear. It is suggested that epigenetic programming, also induced by the adverse intrauterine environment, is a critical underlying mechanism of fetal metabolic programming. Fetal epigenetic programming affects gene expression changes and cellular function through epigenetic modifications without DNA nucleotide sequence changes. Epigenetic modifications can be relatively stably retained and transmitted through mitosis and generations, and thereby induce the development of metabolic syndrome in adult offspring. This manuscript provides an overview of the critical role of epigenetic programming in fetal metabolic programming.